An Investigation of the Major Wheat Weeds in Different Zones of Dera Ismail Khan - Zahid Usman (Journal of Bioresource Management, 2016)
On account of huge yield losses, weed infestation is a serious threat in wheat crops throughout the country. A comprehensive survey to find out the major weeds in wheat in Dera Ismail Khan was carried out during the crop season of 2012-13. Wheat fields at seed farms of Rakhmanghan, RakhZandani, Rata Kulachi and adjacent farmer’s fields to each seed farm were investigated. Data was collected at the peak growth stage of weeds and the quadratic method was used to record relative density (RD), relative frequency (RF), relative crowding coefficient (RCC) and importance value index (IVI). The results revealed that the major and most problematic weed of wheat at all the locations was Avena fatua (wild oat) on account of having maximum IVI at Rakh Manghan (78.51 & 77.44), Rata Kulachi (77.82 & 77.54) and Rakh Zandani (77.51 & 77.53) seed Farms and Farmer’s fields respectively. Rumex dentatus (dock) and Convolvulus arvensis (Lehli) were the second and third abundantly occurring weeds at almost all the seed farms and farmer fields on account of having the second and third highest IVI values at all the locations. Therefore Avena fatua (wildoat), Rumex dentatus (dock) and Convolvulus arvensis (lehli) seed were collected to find out the yield losses through further experimentation.